Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke Within 4.5 h: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials - Muhammad Hassan Waseem (22392178) (2025)
Background Acute ischemic stroke (AIS) requires timely thrombolysis to restore perfusion and minimize neurological damage. Recombinant human prourokinase (rhPro‐UK) has emerged as a promising alternative to alteplase, with potential efficacy and safety benefits within the critical 4.5‐h treatment window. Methods Electronic databases, including PubMed, ScienceDirect, and Cochrane Central, were comprehensively searched from inception until December 2024. Risk ratios (RRs) with 95% confidence intervals were pooled for the dichotomous outcomes using a random effects model in Review Manager software. The heterogeneity among the included trials was evaluated using the I2 statistics, and a sensitivity analysis was conducted to investigate the source of heterogeneity. Results The final statistical analysis included 1179 participants in the rhPro‐UK and 1148 in the tPA group. Excellent functional outcome (modified Rankin Scale [mRS] 0‐1) (RR = 1.04, 95% CI: [0.98, 1.10]; p = 0.16) and good functional outcome (mRS 0‐2) (RR = 1.00, 95% CI: [0.96, 1.05]; p = 0.90; I2 = 0%) were comparable between the two groups. There was also no significant difference in mortality and major neurological improvement. However, there was a trend toward a lower risk of symptomatic intracranial hemorrhage (sICH) in the rhPro‐UK group (RR = 0.53, 95% CI: [0.18, 1.59]; p = 0.26). Conclusion rhPro‐UK demonstrated comparable efficacy to alteplase in achieving functional outcomes in AIS within 4.5 h, with no significant differences in mortality or neurological improvement. Although not statistically significant, a trend toward lower sICH risk with rhPro‐UK highlights its potential safety advantage. More high‐quality randomized clinical trials are required to confirm these findings. Other Information Published in: Brain and Behavior License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/brb3.70420